(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
Natural forest vegetation on Nizhnedneprovski sand area is presented by azonal birch, oak, aspen, alder, poplar and willow-poplar-ash forests belonging to the three classes: Alnetea glutinosae Br.-Bl. et R.Tx. 1943 ex Westhoff et al. 1946, Salicetea purpureae Moor 1958, and Dactylo glomerati – Populetea tremulae Y.O. Vorobyov et I. Solomakha 2014. In forest vegetation Nizhnedneprovskiy sand area 27 sozophytes are present, among them 9 species are included in the Red Data Book of Ukraine, 5 in European Red List, 1 in Bern Convention list, 1 in World Red List and 12 in Red List of Kherson region. The greatest number of species is observed in birch forests (12) and lowest (7) in alder.